Die Familie des Gargilius Martialis. Lokale Gesellschaft und militär im römischen Nordafrika - Herz, Peter (Studia Europaea Gnesnensia, 2017)
The main intention of my paper is to show that the careful interpretation of inscriptions may help us in our understanding of certain historical situation usually treated only superficially by the classical (literary) sources. To achieve such an aim it is necessary to understand such testimonia not as isolated exempla but as parts of much broader historical tradition. I tried to achieve this by integrating the epigraphic sources from other parts of the empire (e.g. Asia Minor) in my study. As a first result we can say that the weakening of the imperial authority in not a local phenomenon of Roman Mauretania, but a phenomenon found in many other regions of the empire. Without the existence of strong local authorities that could act in the place of the emperors the whole empire might have collapsed. The emergence of separate empires (e.g. the imperium Galliarum of Postumus or the regnum Palmyrenorum) may be understood as another facette of this time.